Analisis Afek Variasi Interpersonal dengan Model Dialektologi dalam Talk Show Mata Najwa On Stage - Windi Erica Sari; Gigit Mujianto (Institut Agama Islam Negeri Curup, 2021)
This study aims to identify the form of the social character of the interpersonal affect and the phonological features of the dialectology of the presenter and informants in the Talk Show Mata Najwa On Stage